2006
DOI: 10.1074/jbc.m600697200
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Severe Acute Respiratory Syndrome Coronavirus Receptor-binding Domain Complexed with Neutralizing Antibody

Abstract: The severe acute respiratory syndrome coronavirus (SARSCoV, or SCV), which caused a world-wide epidemic in 2002 and 2003, binds to a receptor, angiotensin-converting enzyme 2 (ACE2), through the receptor-binding domain (RBD) of its envelope (spike, S) glycoprotein. The RBD is very immunogenic; it is a major SCV neutralization determinant and can elicit potent neutralizing antibodies capable of out-competing ACE2. However, the structural basis of RBD immunogenicity, RBD-mediated neutralization, and the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
299
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 254 publications
(307 citation statements)
references
References 42 publications
8
299
0
Order By: Relevance
“…7B), as predicted from the crystal structure of the complex. IgG1 was more potent than Fab, in agreement with its higher effective affinity (avidity) to the surface-associated RBD as measured previously by surface plasmon resonance methodology (36). IgG1 S230.15 also competed with ACE2 for binding to the RBD although at somewhat higher concentration (SI Fig.…”
Section: Potent In Vitro Inhibition Of Entry and Cell Fusion Mediatedsupporting
confidence: 62%
See 1 more Smart Citation
“…7B), as predicted from the crystal structure of the complex. IgG1 was more potent than Fab, in agreement with its higher effective affinity (avidity) to the surface-associated RBD as measured previously by surface plasmon resonance methodology (36). IgG1 S230.15 also competed with ACE2 for binding to the RBD although at somewhat higher concentration (SI Fig.…”
Section: Potent In Vitro Inhibition Of Entry and Cell Fusion Mediatedsupporting
confidence: 62%
“…We have recently identified an hmAb, m396, which binds with high affinity to the RBD, and we determined the crystal structure of the RBD⅐m396 complex at high resolution (36). A crystal structure analysis suggested that this antibody could also neutralize the 2003/2004 outbreak isolate GD03.…”
Section: Potent In Vitro Inhibition Of Entry and Cell Fusion Mediatedmentioning
confidence: 99%
“…This is first time that a neutralizing MAb, i.e., MAbSVP-4, was generated using SVP as an antigen. This result further suggests that SVP carries the neutralizing epitopes that could be viral receptor-binding domains, as indicated by studies of other viruses (12,34). Taken together, we suspect that SVP, as IBDV, is able to interact with cellular receptors.…”
Section: Discussionmentioning
confidence: 58%
“…Fine-mapping studies with peptides or mutant capsids will be necessary to map key interaction residues. Further, cocrystalization of blocking MAbs with the panel of VLPs may provide structural information important for predicting modes of carbohydrate blockade and mapping epitopes onto the structure (52,60). We have shown here by comparing blockade of GII.4-2002 with GII.…”
Section: Discussionmentioning
confidence: 89%